Hybridism and Self-Reconstruction in Joyce Carol Oates’s A Widow’s Story - Pascale Antolin (European Journal of American Studies)
This article analyzes Joyce Carol Oates’s hybridism in her 2011 memoir, A Widow’s Story, as a powerful means of self-assertion and self-reconstruction. It suggests that to write about her painful experience of bereavement Oates resorts to hybridism—generic, narrative and typographic in particular—as it is both a characteristic of her fiction and a means of dramatizing her experience. This hybridism helps her not only express her emotional “derangement” but also recover her identity as a writer. Thus her narrative manifests confusion and continuity, chaos and control, inconsolability and consolation at one and the same time.